Implementation of e-education in Africa via space digital video broadcasting system - Dimov Stojce Ilcev (Bulletin of Electrical Engineering and Informatics, 2020)
This paper introduces an advanced e-education provision via space systems for Africa or any other regions in remote dispersed communities, such as rural, mining, agriculture, surveying, construction, tourism, military and etc. Based on the specific needs and requirements e-education implies significant broadband applications, interconnectivity, and timely and quality-assured content delivery of service. The e-education solutions of distance learning and training for remote and rural areas, which are beyond range of terrestrial and short distance wireless cellular facilities, cannot provide broadband access without space-enabled communication solutions, such as satellite constellations and stratospheric platform systems (SPS) or high altitude platforms (HAP). This paper also discusses the integration challenges that are presented by combining space solutions for implementation e-education and learning in rural and mobile environments. Configuration of in-house development of all segments, installation of the scale-down digital video broadcasting-return channel via satellite (DVB-RCS) hub (gateway), ground network and very small aperture terminal (VSAT), known as fixed interactive terminals (FIT), for e-education, distance learning and staff training initiative in Africa are described.